2018
DOI: 10.1021/acs.molpharmaceut.8b00970
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Single Hydrogen Substitution by Fluorine on the Molecular Interaction and Miscibility between Sorafenib and Polymers

Abstract: We aim to understand the potential impact of a modest chemical modification of a drug molecule on the downstream design of its amorphous solid dispersion (ASD) formulation. To this end, we used sorafenib (SOR) and its fluorinated form, regorafenib (REG), as model drugs, to assess the impact of a single hydrogen substitution by fluorine on the molecular interaction and miscibility between drug and PVP or PVP–VA, two commonly used polymers for ASDs. In this study, we observed that the T g values of PVP or PVP–VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Forster et al have reported the composition dependent presence of single or multiple T g values in the system of lacidipine and indomethacin with PVP . Apart from the presence of multiple T g values, reports also state the presence of a single T g as a sign of the molecularly dispersed ASD. , This is one of the commonly used qualitative predictors of drug-polymer miscibility with more than 50 instances in the reviewed literature. In a most recent report, Blasi et al have reported the presence of multiple T g values for ASD with ketoprofen content more than 35% w/w in poly­(D, L-lactide- co -glycolide) …”
Section: Methods For the Evaluation Of Drug-polymer Solubility And Mi...mentioning
confidence: 99%
“…Forster et al have reported the composition dependent presence of single or multiple T g values in the system of lacidipine and indomethacin with PVP . Apart from the presence of multiple T g values, reports also state the presence of a single T g as a sign of the molecularly dispersed ASD. , This is one of the commonly used qualitative predictors of drug-polymer miscibility with more than 50 instances in the reviewed literature. In a most recent report, Blasi et al have reported the presence of multiple T g values for ASD with ketoprofen content more than 35% w/w in poly­(D, L-lactide- co -glycolide) …”
Section: Methods For the Evaluation Of Drug-polymer Solubility And Mi...mentioning
confidence: 99%
“…Owing to its ecofriendly accountability and bio-competitiveness, bio-degradable polymeric nanoparticles with appropriate dimensions, even surface diameter, and increased aqueous solubility have gotten a lot of attention (Liu et al, 2016 ; Zhang & Tung, 2017 ; Liu et al, 2019 ; Li et al, 2020a , 2020b ). In anticancer therapy, biomaterial fields, and medical diagnosis, a number of environmentally friendly NMs have been widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Some commercial products of non-biodegradable microspheres have come into the market already such as DC Beads and Hepasphere™ for TACE. Drugs especially the positively charged were usually shielded by ion exchange approach, and the drug elution kinetics were determined by the ionic environment of physiological fluids (Liu et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy can be performed via co-administration of a supplementary cancer drug along with a sensitizer. The interfaces within potential anticancer drugs rely on the dose ratios between the two medications and can be potentially incompatible (Li and Finley, 2018 ; Liu et al., 2019 ; Yang et al., 2019 ). Consequently, the importance of preserving a beneficial ratio to maintain a synergistic relationship between two drugs through nanoparticles (NPs) formulations cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation